Prevalence and burden of injuries and illnesses in men's university football players: a prospective cohort study in 2020 competitive season - Sonoko Mashimo; Naruto Yoshida; Takaaki Hogan; Hideaki Waki; Yoichi Minakawa; Shogo Miyazaki; Masaaki Koido (Japanese Society of Physical Fitness and Sports Medicine, 2022)
Despite extensive studies on the incidence and characteristics of football (soccer) injuries using a time-loss definition, the exact magnitude of injuries and illnesses in football players remains unclear. This study aimed to examine the prevalence and burden of health problems among university football players based on all physical complaints. Ninety-four male university football players were prospectively followed up during the 2020 competitive season in Japan. The study period was divided into the self-training period (SP) and the football period (FP). All participants were asked to complete the Japanese version of the Oslo Sports Trauma Research Center Questionnaire on Health Problems (OSTRC-H2.JP) every Sunday. The main outcome measures were the prevalence of all health problems and substantial health problems and their burdens. The average response rate to the OSTRC-H2.JP was 88.8% [95% CI, confidence interval: 87.7%-89.9%]. Overall, the average weekly prevalence of all health problems was 19.7% [95% CI: 18.3%-21.1%]. During the FP, the average weekly prevalence of all health problems and substantial health problems were 22.9% [95% CI: 21.0%-24.7%] and 15.3% [95% CI: 13.7%-16.9%], respectively. Injuries were the main problem, with traumatic injuries in the ankle, thigh, and foot representing the greatest burden. This study indicated that approximately 20% of university football players experienced injuries or illnesses. Traumatic injuries in the ankle, thigh, and foot represented the greatest burden on self-reported reliance using broad definitions of injury and illness. Therefore, injury prevention should focus on preventing these complaints.